The moderating effect of financial condition on the factors influencing taxpayer's compliance behavior in Negeria - Alabede, James O. (World Business Institute, 2011)
Income tax administration in Nigeria as in some other developing countries is characterised by low tax compliance level.A number of factors have been identified in the literature to proffer explanation for such phenomenon. However, the influences of these factors on tax compliance behaviour may be moderated by taxpayer’s financial condition.This study investigates the moderating effect of financial condition on tax compliance behaviour and its determinants. The data of the study which were collected through a survey of individual taxpayers’ opinion were treated statistically using multiple regression.The outcome of the study indicated that in presence of financial condition, greater explanation of tax compliance behaviour is obtained from the determinants.